Yttrium oxide doped C / C-ZrC ceramic-based composite material as well as preparation method and application thereof

By adding rare earth yttrium oxide to zirconium carbide, the phase transition of zirconium oxide is suppressed, and the problem of oxide film peeling of carbon fiber reinforced zirconium carbide ceramic matrix composite material in ultra-high temperature and oxygen environment is solved, and its ablation resistance is improved.

CN119176715AActive Publication Date: 2024-12-24GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI +1

Patent Information

Application Number
CN202411367629.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-24
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Traditional carbon fiber reinforced zirconium carbide ceramic matrix composite materials are prone to fall off due to phase change of zirconium oxide in ultra-high temperature and oxygen environment, reducing the anti-ablation performance.

Method used

Rare earth yttrium oxide is incorporated into zirconium carbide, and stable tetragonal or cubic phase crystals are formed through sonication and high-temperature pyrolysis treatment, which inhibits the phase change of zirconium oxide and maintains the integrity of the oxide layer.

Benefits of technology

It improves the ablation resistance of zirconium carbide ceramic composite materials and extends its service life in ultra-high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176715A_ABST
    Figure CN119176715A_ABST
Patent Text Reader

Abstract

The invention relates to an yttrium oxide doped C / C-ZrC ceramic matrix composite material and a preparation method and application thereof.According to the yttrium oxide doped C / C-ZrC ceramic matrix composite material and the preparation method and application thereof, an yttrium oxide precursor is directly dissolved in an organic solvent containing a zirconium carbide source solution and mixed to obtain a uniform solution, and then an impregnation cracking reaction is conducted. Meanwhile, rare earth elements can be more uniformly doped, the operation method is simpler, more convenient and easier to control, the rare earth oxide is doped into zirconium carbide, the sintering assisting effect can be achieved, the phase of zirconium oxide serving as a main substance of an ablation oxide layer can be stabilized, and the situation that zirconium oxide is subjected to phase transformation from high temperature to low temperature to cause volume change is prevented; therefore, the integrity of the oxide layer is kept, and the ablation resistance of the composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic-based composite materials, and in particular to an yttria-doped C / C-ZrC ceramic-based composite material and a preparation method and application thereof. Background Art

[0002] Carbon / carbon composites refer to carbon fiber reinforced carbon matrix composites. The commonly used carbon / carbon composite matrix is ​​amorphous. Carbon / carbon composites have low density, high specific modulus, high specific strength, good toughness, ablation resistance and thermal shock resistance, small thermal expansion, excellent thermal shock resistance, good friction performance and low wear rate. However, in ultra-high temperature oxygen environment, the rapid oxidation and ablation of the carbon matrix limits its long-term application in extreme ultra-high temperature environment.

[0003] Zirconium carbide ceramics have excellent high temperature resistance and oxidation and ablation resistance, but they also have a fatal disadvantage inherent in ceramics - brittleness. The low fracture toughness of ceramics leads to poor thermal shock resistance, and they are easily damaged during rapid temperature rise and fall. Continuous carbon fiber reinforced zirconium carbide ceramic matrix composites can solve the problem of poor thermal shock resistance of bulk ceramics, making them an important thermal protection material in the fields of new high-speed aircraft and their power systems, and are currently a research hotspot in the field of high-temperature resistant materials.

[0004] The key to the anti-oxidation and ablation of zirconium carbide ceramics and their composite materials is to form a dense oxide film with moderate viscosity on the surface of the material. The oxygen barrier and anti-scouring effect of the oxide film protect the base material. During the service process, the zirconium oxide generated by the oxidation of zirconium carbide has the problem of phase change. In the process of alternating high and low temperature and hot and cold, it will change from tetragonal phase to monoclinic phase. This process causes volume expansion, which causes the oxide film to fall off and the anti-ablation performance to decrease.

[0005] Therefore, based on the traditional carbon fiber reinforced zirconium carbide ceramic-based composite materials, it is easy to cause the oxidation of zirconium carbide to generate zirconium oxide during service, which causes the oxide film to fall off due to phase change problems, and the anti-ablation performance decreases. How to inhibit the phase change of zirconium oxide and improve the anti-ablation performance of zirconium carbide ceramics has become a problem that needs to be solved urgently. Summary of the invention

[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a yttria-doped C / C-ZrC ceramic-based composite material, a preparation method and use thereof. The present invention not only can play a role in sintering by adding rare earth oxides to zirconium carbide, but also can stabilize the phase of zirconium oxide, the main substance of the ablation oxide layer, and prevent the volume change caused by the phase transition of zirconium oxide from high temperature to low temperature, thereby maintaining the integrity of the oxide layer and improving the anti-ablation performance of the composite material.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a yttria-doped C / C-ZrC ceramic-based composite material, the preparation method comprising the following steps:

[0009] (1) mixing a zirconium carbide source solution and a yttrium oxide precursor, and obtaining a preliminary impregnation solution after ultrasonic treatment;

[0010] (2) introducing the preliminary impregnation solution obtained in step (1) into the carbon / carbon composite material to obtain an intermediate;

[0011] (3) subjecting the intermediate obtained in step (2) to high temperature pyrolysis treatment under inert atmosphere to obtain a composite material;

[0012] (4) The composite material obtained is reused with the preliminary impregnation solution of step (1) to cycle through the same impregnation and high-temperature pyrolysis steps as steps (2) and (3) until the density growth rate of the composite material is less than 1%, thereby obtaining the yttria-doped C / C-ZrC ceramic-based composite material.

[0013] The inventors have discovered that low-valent rare earth element cations can stabilize the high-temperature phase of zirconium oxide. By adding rare earth yttrium oxide to zirconium carbide, it can not only aid sintering, but also stabilize the phase of zirconium oxide, the main substance of the ablation oxide layer. When a certain amount of rare earth oxide is introduced into the ZrO2 crystal, the rare earth ions will replace the positions of zirconium ions and generate oxygen vacancies in the lattice. The generation of oxygen vacancies reduces the repulsive force between oxygen and oxygen, making the eight-coordinate structure stable to room temperature, and obtaining room temperature stable tetragonal or cubic phase crystals, that is, inhibiting the phase transition of the ZrO2 crystal from the tetragonal phase to the monoclinic phase, preventing the volume change caused by the phase transition of zirconium oxide from high temperature to low temperature, thereby maintaining the integrity of the oxide layer, reducing or eliminating the volume mutation of zirconium oxide, and improving the anti-ablation performance of the composite material.

[0014] The present invention directly dissolves the yttrium oxide precursor in the zirconium carbide source solution to obtain a uniform precursor impregnation solution, and then performs an impregnation cracking reaction. However, the conventional method of alternately impregnating and cracking a polycarbonate zirconium solution and a rare earth nitrate solution has too low efficiency. The present invention directly dissolves the yttrium oxide precursor in an organic solvent containing a zirconium carbide source solution, mixes to obtain a uniform solution, and then performs an impregnation cracking reaction, which not only improves the impregnation efficiency, but also enables more uniform rare earth element doping, and the operation method is simpler and easier to control.

[0015] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0016] Preferably, the zirconium carbide source solution in step (1) comprises a xylene solution of a zirconium carbide source.

[0017] Preferably, the mass fraction of the zirconium carbide source in the zirconium carbide source solution is 60%-80%, for example, it can be 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79% or 80%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] The present invention preferably has a mass fraction of zirconium carbide source in the zirconium carbide source solution of 60%-80%, at which time the effect is more excellent. The mass of the zirconium carbide source in the zirconium carbide source solution determines the ceramic yield after high-temperature pyrolysis of the precursor and the viscosity of the solution, which will affect the subsequent preparation efficiency of the composite material.

[0019] Preferably, the zirconium carbide source comprises zirconium polypropoxide.

[0020] Preferably, the purity of the zirconium carbide source is ≥ 99.9%.

[0021] Preferably, the yttrium oxide precursor comprises yttrium acetylacetonate.

[0022] The yttrium acetylacetonate used in the present invention can be well dissolved in the zirconium carbide source solution, eliminating the step of dissolving the rare earth element nitrate in water, which not only improves the efficiency, but also the method of impregnating after mixing with the zirconium carbide source solution to obtain a uniform solution can achieve the uniformity of rare earth element doping.

[0023] Preferably, the purity of the yttrium acetylacetonate is ≥99.9%.

[0024] Preferably, the yttrium acetylacetonate does not contain crystal water.

[0025] Preferably, the median particle size of the yttrium acetylacetonate is 50μm-75μm, for example, it can be 50μm, 51μm, 52μm, 53μm, 54μm, 55μm, 56μm, 57μm, 58μm, 59μm, 60μm, 61μm, 62μm, 63μm, 64μm, 65μm, 66μm, 67μm, 68μm, 69μm, 70μm, 71μm, 72μm, 73μm, 74μm or 75μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] Preferably, based on the total mass of the zirconium carbide source and the yttrium oxide precursor as 100%, the mass fraction of the yttrium oxide precursor in step (1) is 2.5%-10%, for example, it can be 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0027] The present invention preferably has a mass fraction of 2.5%-10% of the yttria precursor. The amount of yttria precursor added directly affects the stability of the zirconium oxide crystal. When the mass fraction of the yttria precursor is lower than 2.5%, the effect of stabilizing the zirconium oxide is very weak. When the mass fraction of the yttria precursor reaches 10%, the crystal stability of the zirconium oxide is basically achieved. If the yttria precursor continues to be added, and its mass fraction is higher than 10%, it will lead to a relative reduction in the ultra-high temperature ceramic zirconium carbide phase, resulting in a decrease in the anti-ablation performance.

[0028] Preferably, the ultrasonic treatment time in step (1) is 0.5h-1h, for example, 0.5h, 0.8h or 1h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0029] In the present invention, a zirconium carbide source solution and a yttrium oxide precursor are mixed, and then ultrasonic treatment is performed to improve the uniformity of the solution, so as to achieve molecular-level mixing of the zirconium carbide source and the yttrium oxide source, and finally improve the element uniformity of the ceramic.

[0030] Preferably, the introducing method in step (2) comprises vacuum impregnation or pressure impregnation.

[0031] Preferably, the absolute vacuum degree of the vacuum impregnation is equal to or less than 100 Pa, for example, it can be 10 Pa, 50 Pa, 80 Pa, 90 Pa or 100 Pa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] Preferably, the vacuum impregnation time is 0.5 h-2 h, for example, 0.5 h, 1 h, 1.5 h or 2 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0033] Preferably, the pressure of the pressure impregnation is 2 MPa-4 MPa, for example, 2 MPa, 2.5 MPa, 3 MPa, 3.5 MPa or 4 MPa, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0034] Preferably, the pressure impregnation time is 0.5h-1h, for example, 0.5h, 0.8h or 1h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0035] Preferably, the method for preparing the carbon / carbon composite material of the present invention comprises the following steps:

[0036] The carbon fiber braid purchased from Anhui Qingshui Lake New Material Technology Co., Ltd. is treated by chemical vapor deposition (the carbon source precursor is methane), and the methane is cracked under vacuum conditions at a certain temperature and pressure, and the generated carbon is gradually deposited into the pores of the molded porous preform reinforced skeleton until the carbon / carbon composite material described in the present invention is uniformly obtained.

[0037] Preferably, the density of the carbon / carbon composite material in step (2) is 1.0 g / cm 3 -1.4g / cm 3 , for example, it can be 1.0 g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 or 1.4 g / cm 3 , but not limited to the listed values, other unlisted values ​​within the numerical range are also applicable.

[0038] Preferably, the porosity of the carbon / carbon composite material in step (2) is 23%-45%, for example, it can be 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44% or 45%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0039] The density of the carbon / carbon composite material is adapted to the size of the porosity. The higher the density of the carbon / carbon composite material, the smaller the porosity of the corresponding carbon / carbon composite material will be.

[0040] Preferably, the inert gas in step (3) comprises argon.

[0041] Preferably, the inert gas flow rate in step (3) is 0.3 L / min-0.5 L / min, for example, 0.3 L / min, 0.4 L / min or 0.5 L / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0042] Preferably, the temperature of the high temperature pyrolysis treatment in step (3) is 1600°C-1700°C, for example, it can be 1600°C, 1610°C, 1620°C, 1630°C, 1640°C, 1650°C, 1660°C, 1670°C, 1680°C, 1690°C or 1700°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0043] In the present invention, the preferred high-temperature pyrolysis treatment temperature is 1600°C-1700°C. If the pyrolysis treatment temperature is too low, zirconium oxide cannot be completely converted into zirconium carbide through the carbon thermal reduction process, thereby corroding the carbon / carbon composite material and reducing the mechanical properties of the composite material.

[0044] Preferably, the heating rate of the high temperature pyrolysis treatment in step (3) is 1°C / min-5°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] Preferably, the time of the high temperature pyrolysis treatment in step (3) is 1 h-3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0046] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:

[0047] (1) mixing a zirconium carbide source solution and a yttrium oxide precursor with a mass fraction of 60% to 80%, and ultrasonically treating the mixture for 0.5 h to 1 h to obtain a preliminary impregnation solution;

[0048] (2) The preliminary impregnation solution obtained in step (1) is introduced into a molten metal having a density of 1.0 g / cm by an impregnation method or a pressure impregnation method. 3 -1.4g / cm 3 , a carbon / carbon composite material having a porosity of 23%-45% to obtain an intermediate;

[0049] (3) heating the intermediate obtained in step (2) to 1600° C.-1700° C. at a heating rate of 1° C. / min-5° C. / min under inert gas protection for 1 h-3 h to obtain a composite material;

[0050] (4) using the initial impregnation solution of step (1) to cycle through the obtained composite material and alternately perform the same impregnation and high-temperature pyrolysis steps as steps (2) and (3) until the density growth rate of the composite material is less than 1%, thereby obtaining the yttria-doped C / C-ZrC ceramic-based composite material;

[0051] Based on the total mass of the zirconium carbide source and the yttria precursor being 100%, the mass fraction of the yttria precursor in step (1) is 2.5%-10%;

[0052] The absolute vacuum degree of the vacuum impregnation is equal to or less than 100 Pa; the time of the vacuum impregnation is 0.5h-2h;

[0053] The pressure of the pressure impregnation is 2MPa-4MPa; the time of the pressure impregnation is 0.5h-1h.

[0054] In a second aspect, the present invention provides a yttria-doped C / C-ZrC ceramic-based composite material prepared by the preparation method described in the first aspect.

[0055] The yttria-doped C / C-ZrC ceramic-based composite material provided by the present invention uses rare earth yttria-doped zirconium carbide as a matrix and carbon fiber as a reinforcing phase. The ceramic-based composite material not only uses zirconium carbide with excellent ablation resistance as a matrix, but also the carbon fiber improves the overall mechanical strength of the material.

[0056] Preferably, the yttria-doped C / C-ZrC ceramic-based composite material comprises a carbon / carbon composite material and a yttria-doped ZrC ceramic matrix.

[0057] Preferably, based on the total volume of the yttria-doped C / C-ZrC ceramic-based composite material being 100%, the volume fraction of the carbon fiber is 45%-50%, for example, 45%, 46%, 47%, 48%, 49% or 50%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0058] Preferably, based on the total volume of the yttria-doped C / C-ZrC ceramic-based composite material being 100%, the volume fraction of the carbon matrix is ​​15%-20%, for example, 15%, 16%, 17%, 18%, 19% or 20%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0059] Preferably, based on the total volume of the yttria-doped C / C-ZrC ceramic-based composite material as 100%, the volume fraction of the yttria-doped ZrC ceramic matrix is ​​20%-30%, for example, it can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or 30%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] In a third aspect, the present invention provides a use of a yttria-doped C / C-ZrC ceramic-based composite material as described in the second aspect or a rare earth oxide-doped C / C-ZrC ceramic-based composite material prepared by the preparation method described in the first aspect, wherein the yttria-doped C / C-ZrC ceramic-based composite material is used in the field of ultra-high temperature ceramics.

[0061] The yttria-doped C / C-ZrC ceramic matrix composite material provided by the present invention is used in the field of ultra-high temperature ceramics. The introduction of rare earth oxides improves the anti-ablation performance of the C / C-ZrC ceramic matrix composite material, making it possible to reuse it.

[0062] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0063] Compared with the prior art, the present invention has at least the following beneficial effects:

[0064] (1) The yttria-doped C / C-ZrC ceramic-based composite material provided by the present invention can not only play a role in sintering by adding rare earth yttria into zirconium carbide, but also stabilize the phase of zirconium oxide, the main substance of the ablated oxide layer, and prevent the volume change caused by the phase transition of zirconium oxide from high temperature to low temperature, thereby maintaining the integrity of the oxide layer. The introduction of rare earth oxide improves the anti-ablation performance of the C / C-ZrC ceramic-based composite material, making it possible for it to be reused.

[0065] (2) The present invention adopts the method of directly dissolving the yttrium oxide precursor in the organic solvent containing the zirconium carbide source solution, mixing to obtain a uniform solution and then performing an impregnation cracking reaction. The preparation method of the present invention not only improves the efficiency of impregnation, but also enables the rare earth element doping to be more uniform, and the operation method is simpler and easier to control. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 This is a flow chart of preparing the yttria-doped C / C-ZrC ceramic-based composite material according to Example 1 of the present invention;

[0067] Figure 2 This is a macroscopic morphology of the yttria-doped C / C-ZrC ceramic matrix composite material prepared in Example 1 of the present invention after ablation at 2000° C.;

[0068] Figure 3 This is a macroscopic morphology of the yttria-doped C / C-ZrC ceramic matrix composite material prepared in Example 2 of the present invention after ablation at 2000° C.;

[0069] Figure 4This is a macroscopic morphology of the C / C-ZrC ceramic matrix composite material prepared in Comparative Example 1 of the present invention after ablation at 2000°C;

[0070] Figure 5 This is a macroscopic morphology of the yttria-doped C / C-ZrC ceramic matrix composite material prepared in Example 1 of the present invention after ablation at 2400° C.;

[0071] Figure 6 This is a macroscopic morphology of the C / C-ZrC ceramic matrix composite material prepared in Comparative Example 1 of the present invention after ablation at 2400°C;

[0072] Figure 7 It is the XRD spectrum of the ceramic-based composite materials prepared in Examples 1, 2, 4 and Comparative Example 1 of the present invention after ablation at 2000°C. DETAILED DESCRIPTION

[0073] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0074] In the following examples, unless otherwise specified, all reagents and consumables were purchased from conventional reagent manufacturers in the field; unless otherwise specified, the experimental methods and technical means used were conventional methods and means in the field.

[0075] Example 1

[0076] The specific process flow of the yttria-doped C / C-ZrC ceramic matrix composite material provided in this embodiment is as follows: Figure 1 As shown, the preparation method comprises the following steps:

[0077] (1) mixing a xylene solution of 66.7% poly(zirconium) propoxide (CAS No.: 23519-77-9) and yttrium acetylacetonate, and ultrasonically treating for 0.5 h to obtain a preliminary impregnation solution;

[0078] Based on the total mass of zirconium polypropoxide and yttrium acetylacetonate as 100%, the mass fraction of yttrium acetylacetonate in step (1) is 5%;

[0079] (2) Under the condition of vacuum degree of 100 Pa, the preliminary impregnation solution obtained in step (1) was introduced into a vacuum chamber with a density of 1.2 g / cm 3 , in a carbon / carbon composite material with a porosity of 30%, the intermediate is obtained by immersing for 0.5 h;

[0080] (3) placing the intermediate obtained in step (2) in a tubular furnace, under the protection of argon gas, introducing argon gas at a flow rate of 0.4 L / min, heating to 1600° C. at a heating rate of 5° C. / min, and performing high-temperature pyrolysis treatment for 1 h to obtain a composite material;

[0081] (4) The composite material obtained is reused with the preliminary impregnation solution of step (1) to cycle through the same impregnation and high-temperature pyrolysis steps as steps (2) and (3) until the density growth rate of the composite material is less than 1%, thereby obtaining the yttria-doped C / C-ZrC ceramic-based composite material.

[0082] The macroscopic morphology of the prepared yttria-doped C / C-ZrC ceramic matrix composite material after ablation at 2000°C is shown in the figure. Figure 2 As shown in the figure, it can be seen that the formed oxide layer has not fallen off.

[0083] The macroscopic morphology of the prepared yttria-doped C / C-ZrC ceramic matrix composite material after ablation at 2400°C is shown in Figure 5 As shown in the figure, it can be seen that the oxide layer has not fallen off and is relatively dense.

[0084] The XRD phase spectrum of the prepared yttria-doped C / C-ZrC ceramic matrix composite material after ablation at 2400°C is shown in Figure 7 As shown in the figure, it can be seen that after doping with yttrium acetylacetonate, the peak of monoclinic zirconia weakens and the peak of tetragonal zirconia strengthens. That is, yttrium oxide stabilizes part of zirconia, reduces the volume expansion caused by phase change, thereby reducing its mass ablation rate and improving its anti-ablation performance.

[0085] Example 2

[0086] The preparation method of the yttria-doped C / C-ZrC ceramic matrix composite material provided in this embodiment comprises the following steps:

[0087] (1) mixing a xylene solution of 72% poly(zirconium) propoxide and yttrium acetylacetonate, and ultrasonically treating for 1 h to obtain a preliminary impregnation solution;

[0088] Based on the total mass of zirconium polypropoxide and yttrium acetylacetonate as 100%, the mass fraction of yttrium acetylacetonate in step (1) is 10%;

[0089] (2) Under the condition of vacuum degree of 50 Pa, the preliminary impregnation solution obtained in step (1) was introduced into a vacuum chamber with a density of 1.1 g / cm 3 , in a carbon / carbon composite material with a porosity of 39%, the intermediate is obtained by immersing for 0.5 h;

[0090] (3) placing the intermediate obtained in step (2) in a tubular furnace, under the protection of argon gas, introducing argon gas at a flow rate of 0.5 L / min, heating to 1700° C. at a heating rate of 5° C. / min, and performing high-temperature pyrolysis treatment for 1 h to obtain a composite material;

[0091] (4) The composite material obtained is reused with the preliminary impregnation solution of step (1) to cycle through the same impregnation and high-temperature pyrolysis steps as steps (2) and (3) until the density growth rate of the composite material is less than 1%, thereby obtaining the yttria-doped C / C-ZrC ceramic-based composite material.

[0092] The macroscopic morphology of the prepared yttria-doped C / C-ZrC ceramic matrix composite material after ablation at 2400°C is shown in Figure 3 As shown in the figure, it can be seen that the oxide layer is relatively dense and no obvious ablation pits appear.

[0093] Example 3

[0094] The preparation method of the yttria-doped C / C-ZrC ceramic matrix composite material provided in this embodiment comprises the following steps:

[0095] (1) mixing a xylene solution of 60% poly(zirconium) propoxide and yttrium acetylacetonate, and ultrasonically treating for 0.5 h to obtain a preliminary impregnation solution;

[0096] Based on the total mass of zirconium polypropoxide and yttrium acetylacetonate as 100%, the mass fraction of yttrium acetylacetonate in step (1) is 15%;

[0097] (2) Under the condition of vacuum degree of 100 Pa, the preliminary impregnation solution obtained in step (1) was introduced into a vacuum chamber with a density of 1.3 g / cm 3 , in a carbon / carbon composite material with a porosity of 28%, the impregnation method is pressure impregnation, the impregnation pressure is 2 MPa, and the impregnation time is 0.5 h to obtain an intermediate;

[0098] (3) placing the intermediate obtained in step (2) in a tubular furnace, under the protection of argon gas, introducing argon gas at a flow rate of 0.3 L / min, heating the temperature to 1650° C. at a heating rate of 3° C. / min, and performing high-temperature pyrolysis treatment for 1 h to obtain a composite material;

[0099] (4) The composite material obtained is reused with the preliminary impregnation solution of step (1) to cycle through the same impregnation and high-temperature pyrolysis steps as steps (2) and (3) until the density growth rate of the composite material is less than 1%, thereby obtaining the yttria-doped C / C-ZrC ceramic-based composite material.

[0100] Example 4

[0101] This embodiment provides a yttria-doped C / C-ZrC ceramic-based composite material, which is different from Embodiment 1 only in that, when preparing the yttria-doped C / C-ZrC ceramic-based composite material, the mass fraction of yttrium acetylacetonate added in step (1) is 1%, based on the total mass of zirconium polypropoxide and yttrium acetylacetonate as 100%, and the remaining steps remain unchanged.

[0102] Example 5

[0103] This embodiment provides a yttria-doped C / C-ZrC ceramic-based composite material, which is different from Example 1 only in that, when preparing the yttria-doped C / C-ZrC ceramic-based composite material, the mass fraction of yttrium acetylacetonate added in step (1) is 20%, based on the total mass of zirconium polypropoxide and yttrium acetylacetonate as 100%, and the remaining steps remain unchanged.

[0104] Example 6

[0105] This embodiment provides a yttria-doped C / C-ZrC ceramic-based composite material, which is different from Example 1 only in that, when preparing the yttria-doped C / C-ZrC ceramic-based composite material, the mass fraction of the xylene solution of polypropyl zirconium oxide described in step (1) is 50%, and the other steps remain unchanged.

[0106] Comparative Example 1

[0107] This comparative example provides a C / C-ZrC ceramic matrix composite material, which is different from Example 1 only in that, when preparing the C / C-ZrC ceramic matrix composite material, yttrium acetylacetonate is not added in step (1), and the other steps remain unchanged.

[0108] The macroscopic morphology of the prepared C / C-ZrC ceramic matrix composite material after ablation at 2000℃ is shown in Figure 4 As shown in the figure, it can be seen that the formed oxide layer falls off.

[0109] The macroscopic morphology of the prepared C / C-ZrC ceramic matrix composite material after ablation at 2400℃ is shown in Figure 6 As shown in the figure, it can be seen that the entire layer of the composite material has fallen off.

[0110] The XRD phase spectrum of the prepared C / C-ZrC ceramic matrix composite material after ablation at 2000℃ is as follows: Figure 7 As shown in the figure, it can be seen that without doping yttrium acetylacetonate, the physical phase of the generated zirconium oxide is monoclinic zirconium oxide.

[0111] Comparative Example 2

[0112] This comparative example provides a C / C-ZrC ceramic-based composite material. When preparing the C / C-ZrC ceramic-based composite material, a batch impregnation method is adopted. The specific preparation method is as follows:

[0113] (1) dissolving zirconium polypropoxide in xylene to obtain zirconium polypropoxide with a mass fraction of 66.7%;

[0114] (2) dissolving rare earth yttrium nitrate in deionized water to prepare a 25 wt % solution;

[0115] (3) Under the condition of vacuum degree of 100Pa, alternately introduce density of 1.2g / cm 3 , a carbon / carbon composite material with a porosity of 30% is first impregnated with a zirconium carbide source solution with a mass fraction of 66.7%, and then placed in a tubular furnace, and heated to 1600°C at a heating rate of 5°C / min for 1h under argon protection, with an argon flow rate of 0.4L / min, to obtain a first intermediate;

[0116] (4) impregnating the first intermediate obtained in step (3) with an aqueous solution of yttrium nitrate, and then placing it in a tubular furnace, under the protection of argon gas, introducing argon gas at a flow rate of 0.4 L / min, heating the temperature to 1600° C. at a heating rate of 5° C. / min, and performing high-temperature pyrolysis treatment for 1 h to obtain a second intermediate;

[0117] (5) The obtained second intermediate is then subjected to the same impregnation and high-temperature pyrolysis steps as in step (3) and step (4) by using the zirconium carbide source solution of step (1) and the yttrium nitrate aqueous solution of step (2) in a cycle, until the density growth rate of the composite material is less than 1%, thereby obtaining the yttrium oxide-doped C / C-ZrC ceramic-based composite material.

[0118] The operating steps for testing the ablation rate are as follows: Cut a sample of standard size (5cm×5cm). Place the sample under a high-temperature ablation furnace or plasma torch. Perform ablation at temperatures of 2000℃ and 2400℃ in an argon atmosphere, and record the ablation time. After ablation, the sample is cooled naturally to room temperature. Use a precision balance to measure the mass of the sample before and after ablation. Measure the dimensional change of the sample before and after ablation. Calculate the ablation rate (mg / s) based on the mass loss and dimensional change.

[0119] Table 1

[0120]

[0121] The test results show that:

[0122] (1) It can be seen from Examples 1-3 that the present invention can not only play a role in sintering by adding rare earth yttrium oxide to zirconium carbide, but also stabilize the phase of zirconium oxide, the main substance of the ablation oxide layer, and prevent the volume change caused by the phase transition of zirconium oxide from high temperature to low temperature, thereby maintaining the integrity of the oxide layer. The introduction of rare earth oxide improves the ablation resistance of C / C-ZrC ceramic-based composite materials and provides the possibility for their repeated use.

[0123] (2) By comparing Example 1 with Examples 4-5, it can be seen that the present invention has a better effect by further controlling the mass fraction of the yttrium oxide precursor to 2.5-10%. The addition amount of the yttrium oxide precursor directly affects the crystalline stability of zirconium oxide. When the mass fraction of the yttrium oxide precursor is lower than 2.5%, the effect of stabilizing zirconium oxide is very weak.

[0124] (3) By comparing Example 1 with Example 6, it can be seen that the present invention achieves even better results by further controlling the mass fraction of the zirconium carbide source in the zirconium carbide source solution to 60%-80%. If the concentration is too low, the number of immersion cycles will be particularly large, which is time-consuming and labor-intensive.

[0125] (4) It can be seen from Example 1 and Comparative Example 1 that when no rare earth element is introduced, the zirconium oxide generated by oxidation of zirconium carbide undergoes a serious phase change and its ablation rate increases.

[0126] (5) It can be seen from Example 1 and Comparative Example 2 that when yttrium nitrate is used as a rare earth element source, since yttrium nitrate cannot be dissolved in the zirconium carbide precursor, the raw materials need to be dissolved separately to obtain two impregnation solutions. The batch impregnation method will result in yttrium oxide and zirconium carbide being unable to achieve molecular-level mixing, and the preparation cycle is also significantly increased. The present invention uses yttrium acetylacetonate as a yttrium oxide source, which can be well dissolved in the zirconium carbide solution during the preparation process, which not only introduces rare earth elements but also reduces the impregnation cycle, thereby achieving a better doping effect.

[0127] In summary, the yttria-doped C / C-ZrC ceramic-based composite material provided by the present invention uses rare earth yttria-doped zirconium carbide as a matrix and carbon fiber as a reinforcing phase. The ceramic-based composite material not only uses zirconium carbide with excellent ablation resistance as a matrix, but also the carbon fiber improves the overall mechanical strength of the material. In addition, the present invention adopts the method of directly dissolving the yttria precursor in an organic solvent containing a zirconium carbide source solution, mixing to obtain a uniform solution, and then performing an impregnation cracking reaction. The preparation method of the present invention not only improves the efficiency of impregnation, but also enables rare earth element doping to be more uniform, and the operation method is simpler and easier to control.

[0128] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a yttria-doped C / C-ZrC ceramic matrix composite material, characterized in that: The preparation method comprises the following steps: (1) mixing a zirconium carbide source solution and a yttrium oxide precursor, and obtaining a preliminary impregnation solution after ultrasonic treatment; (2) introducing the preliminary impregnation solution obtained in step (1) into the carbon / carbon composite material to obtain an intermediate; (3) subjecting the intermediate obtained in step (2) to high temperature pyrolysis treatment under the protection of an inert gas to obtain a composite material; (4) The composite material obtained is reused with the preliminary impregnation solution of step (1) to cycle through the same impregnation and high-temperature pyrolysis steps as steps (2) and (3) until the density growth rate of the composite material is less than 1%, thereby obtaining the yttria-doped C / C-ZrC ceramic-based composite material.

2. The preparation method according to claim 1, characterized in that: The zirconium carbide source solution in step (1) comprises a xylene solution of the zirconium carbide source; Preferably, the mass fraction of the zirconium carbide source in the zirconium carbide source solution is 60%-80%.

3. The preparation method according to claim 2, characterized in that: The zirconium carbide source includes zirconium polypropoxide; Preferably, the yttrium oxide precursor comprises yttrium acetylacetonate; Preferably, the median particle size of the yttrium acetylacetonate is 50 μm-75 μm.

4. The preparation method according to claim 2 or 3, characterized in that: Based on the total mass of the zirconium carbide source and the yttria precursor being 100%, the mass fraction of the yttria precursor in step (1) is 2.5%-10%; Preferably, the ultrasonic treatment time in step (1) is 0.5h-1h.

5. The preparation method according to claim 1, characterized in that: The method of introducing in step (2) includes vacuum impregnation or pressure impregnation; Preferably, the absolute vacuum degree of the vacuum impregnation is equal to or less than 100 Pa; Preferably, the vacuum impregnation time is 0.5h-2h; Preferably, the pressure of the pressure impregnation is 2MPa-4MPa; Preferably, the pressure impregnation time is 0.5h-1h.

6. The preparation method according to claim 1, characterized in that: The density of the carbon / carbon composite material in step (2) is 1.0 g / cm 3 -1.4g / cm 3 ; Preferably, the porosity of the carbon / carbon composite material in step (2) is 23%-45%.

7. The preparation method according to claim 1, characterized in that: The inert gas in step (3) comprises argon; Preferably, the inert gas in step (3) has an inlet flow rate of 0.3 L / min-0.5 L / min; Preferably, the temperature of the high temperature pyrolysis treatment in step (3) is 1600° C.-1700° C.; Preferably, the heating rate of the high temperature pyrolysis treatment in step (3) is 1°C / min-5°C / min; Preferably, the high temperature pyrolysis treatment time in step (3) is 1h-3h.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) mixing a zirconium carbide source solution and a yttrium oxide precursor with a mass fraction of 60% to 80%, and ultrasonically treating the mixture for 0.5 h to 1 h to obtain a preliminary impregnation solution; (2) The preliminary impregnation solution obtained in step (1) is introduced into a solution having a density of 1.0 g / cm by immersion or pressure impregnation. 3 -1.4g / cm 3 , a carbon / carbon composite material having a porosity of 23% to 45% to obtain an intermediate; (3) heating the intermediate obtained in step (2) to 1600° C.-1700° C. at a heating rate of 1° C. / min-5° C. / min under inert gas protection for 1 h-3 h to obtain a composite material; (4) using the initial impregnation solution of step (1) to cycle through the obtained composite material and alternately perform the same impregnation and high-temperature pyrolysis steps as steps (2) and (3) until the density growth rate of the composite material is less than 1%, thereby obtaining the yttria-doped C / C-ZrC ceramic-based composite material; Based on the total mass of the zirconium carbide source and the yttria precursor being 100%, the mass fraction of the yttria precursor in step (1) is 2.5%-10%; The absolute vacuum degree of the vacuum impregnation method is equal to or less than 100 Pa; the time of the vacuum impregnation method is 0.5h-2h; The pressure of the pressure impregnation method is 2MPa-4MPa; the time of the pressure impregnation method is 0.5h-1h.

9. A yttria-doped C / C-ZrC ceramic matrix composite material, characterized in that: The yttria-doped C / C-ZrC ceramic-based composite material is prepared according to the preparation method according to any one of claims 1-8.

10. Use of the yttria-doped C / C-ZrC ceramic-based composite material according to claim 9 or the yttria-doped C / C-ZrC ceramic-based composite material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The yttria-doped C / C-ZrC ceramic-based composite material is used in the field of ultra-high temperature ceramics.

Citation Information

Patent Citations

  • One-way high-temperature-resistant and ablation-resistant ceramic-based composite material and preparation method thereof

    CN115340397A

  • Preparation method of rare earth oxide modified C / (C-) SiC-ZrC composite material

    CN116178051A

  • Rare earth composite zirconium carbide-silicon carbide ceramic as well as preparation method and application thereof

    CN117362038A

  • Toughened ceramic-based composite material and preparation method thereof

    CN117586013A

  • High-sintering-degree ceramic-based composite material and preparation method thereof

    CN117602943A

Cited By

  • Automobile flame-retardant carbon fiber sheet and preparation method thereof

    CN121517845A